Furin‐mediated protein processing in infectious diseases and cancer. Issue 8 (5th August 2019) - Braun, Elisabeth; Sauter, Daniel
Abstract: Proteolytic cleavage regulates numerous processes in health and disease. One key player is the ubiquitously expressed serine protease furin, which cleaves a plethora of proteins at polybasic recognition motifs. Mammalian substrates of furin include cytokines, hormones, growth factors and receptors. Thus, it is not surprising that aberrant furin activity is associated with a variety of disorders including cancer. Furthermore, the enzymatic activity of furin is exploited by numerous viral and bacterial pathogens, thereby enhancing their virulence and spread. In this review, we describe the physiological and pathophysiological substrates of furin and discuss how dysregulation of a simple proteolytic cleavage event may promote infectious diseases and cancer. One major focus is the role of furin in viral glycoprotein maturation and pathogenicity. We also outline cellular mechanisms regulating the expression and activation of furin and summarise current approaches that target this protease for therapeutic intervention. Abstract : The serine protease furin regulates numerous processes in health and disease and has become a promising target for the treatment of viral and bacterial infections, as well as cancer. This review provides an overview of proteins that are proteolytically processed by furin, with a major focus on the maturation of viral glycoproteins. It discusses cellular mechanisms regulating furin expression and describes how this protease may be targeted to treat infectious and noninfectious diseases.